Diversidade Cultural: Relatos do Brasil e Argentina - Rossi, Célia Regina [UNESP]; Bochini, Ana Gouvêa [UNESP]; Vilaronga, Carla Ariela Rios [UNESP]; Silva, Luciana Leandro da (Universidade Estadual Paulista (Unesp), 2006)
Este artigo relata duas experiências de projetos realizados em escolas de ensino fundamental, cuja temática foi o trabalho com a diversidade cultural, a valorização de outras culturas e reflexões sobre a própria cultura. O trabalho foi realizado em duas escolas: uma no estado de São Paulo, na cidade de Rio Claro, onde a temática trabalhada foi o Hip-Hop e as manifestações culturais locais brasileiras; a segunda, na capital de uma província Argentina, na cidade de Paraná, onde se trabalhou o contato e a relação entre as manifestações culturais do Brasil e da Argentina. O objetivo central desse trabalho foi pensar caminhos que pudessem levar à construção de uma escola que considerasse as diferenças e a aprendizagem que acontece quando estas (as diferenças) estão em relação.

This article tells two experiences of projects carried through in schools of basic education whose thematic it was the work with the cultural diversity, the valuation of other cultures and reflections on the proper culture The work was carried through in two schools: one in the state of São Paulo, the city of Rio Claro where as the thematic one worked was the Hip-Hop and cultural manifestations local Brazilians the second in the capital of a Argentina province, in the city of Paraná where it worked the contact and the relation enter the cultural manifestations of Brazil and Argentina The central objective of this work was to think ways that could lead to the construction of a school that it considered the differences and the learning that happens when these (the differences) they are in relation.
Cultural Diversity: Reports from Brazil and Argentina
Keywords: Diversidade Cultural; Preconceito; Alteridade; Aprendizagem; Experiência Corporal